Web-based Management Information System of Cases Filed with National Labor Relations Commission - Dela Rosa, Aaron Paul Mallari (International Journal of Computing Sciences Research; Vol 7 (2023): Volume 7, 2023)
Purpose – This study was developed to describe the daily operations and encountered problems of the National Labor Relations Commission Regional Arbitration Branch No. IV (NLRC RAB IV) through conducted observations and interviews. These problems were addressed and analyzed to be the features of the developed web-based management information system (MIS) for cases. Method – The research methodology utilized in this project was the descriptive developmental approach. The Agile Software Development methodology was followed to develop the system. It was used to quickly produce the desired output while allowing the user to go back through phases without finishing the whole cycle. Results – The system covered managing filed complaints, Single-Entry Approach (SEnA), labor cases, and report generation. The findings, through the interview, of handling records were inconsistent and inaccurate. This study also focused on ensuring the Data Privacy Act of 2012, protecting the database's information using the XOR Cipher Algorithm. This study was evaluated using standard web evaluation criteria. Using the criteria, the study's overall mean was 4.27 and 4.43, with the descriptive meaning of Very Good , which showed that the system was accepted as perceived by experts and end-users, respectively. Conclusion – Management of filed cases is a vital process for the Commission. With that said, developing the web-based management information system could ease the internal operations of handling and managing filed labor cases. Moreover, respondents and complainants can easily determine their filed cases' status using the case status tracking system. Recommendations – For further improvements to the system, additional printable documents may be added that could be found needed by the Commission. Moreover, completion of the software development methodology may be done to complete the cycle. Lastly, further research about the effectiveness of the web-based system may be conducted for further enhancements of the system. Research Implications – Services of the Commission may be enhanced upon the implementation of the developed web-based management information system of filed cases. Additionally, offices will have ease of access with the provision of different user levels of access.